Distributed intelligent robotics : research & development in fault-tolerant control and size/position identification : a thesis presented in partial fulfilment of the requirements for the degree of Master of Engineering in Computer Systems Engineering at Massey University - Subramaniam, Karthikeya Krishna (Massey University, 2002)
This thesis presents research conducted on aspects of intelligent robotic systems. In the past two decades, robotics has become one of the most rapidly expanding and developing fields of science. Robotics can be considered as the science of using artificial intelligence in the physical world. Many areas of study exist in robotics. Among these, two fields that are of paramount importance in real world applications are fault tolerance, and sensory systems. Fault tolerance is necessary since a robot in the real world could encounter internal faults, and may also have to continue functioning under adverse conditions. Sensory mechanisms are essential since a robot will possess little intelligence if it does not have methods of acquiring information about its environment. Both these fields are researched in this thesis. In particular, emphasis is placed on distributed intelligent autonomous systems. Experiments and simulations have been conducted to investigate design for fault tolerance. A suitable platform was also chosen for an implementation of a visual system, as an example of a working sensory mechanism.
Keywords: Robotics; Autonomous robots